Associations between brain activity and endogenous and exogenous cortisol – A systematic review. (October 2020) - Harrewijn, Anita; Vidal-Ribas, Pablo; Clore-Gronenborn, Katharina; Jackson, Sarah M.; Pisano, Simone; Pine, Daniel S.; Stringaris, Argyris
Highlights: We reviewed relations between endogenous/exogenous cortisol and human brain function. Studies reported inconsistent findings, due to heterogeneity in methods and analyses. Associations between cortisol and amygdala activity were most consistently found. Abstract: To arrive at a coherent understanding of the relation between glucocorticoids and the human brain, we systematically reviewed the literature for studies examining the associations between endogenous or exogenous cortisol and human brain function. Higher levels of endogenous cortisol during psychological stress were related to increased activity in the middle temporal gyrus and perigenual anterior cingulate cortex (ACC), decreased activity in the ventromedial prefrontal cortex, and altered function (i.e., mixed findings, increased or decreased) in the amygdala, hippocampus and inferior frontal gyrus. Moreover, endogenous cortisol response to psychological stress was related to increased activity in the inferior temporal gyrus and altered function in the amygdala during emotional tasks that followed psychological stress. Exogenous cortisol administration was related to increased activity in the postcentral gyrus, superior frontal gyrus and ACC, and altered function in the amygdala and hippocampus during conditioning, emotional and reward-processing tasks after cortisol administration. These findings were in line with those from animal studies on amygdala activity during and after stress.